Design and Simulation of Innovative QCA Quaternary Logic Gates. Issue 9 (28th July 2021) - Akbari‐Hasanjani, Reza; Sabbaghi‐Nadooshan, Reza
Abstract: This paper proposes a new cell configuration for quaternary Quantum Cellular Automata (QQCA) based on the calculation of polarization. The proposed QQCA cell is based on a three‐particle system that creates instability within a cell in the gate design. Therefore, a single‐particle system or binary QCA (bQCA) technology and a two‐particle system or Ternary QCA (TQCA) technology have been used to implement quaternary logic. The proposed cell can be implemented in two layers or in one, using input and output drives. According to the dimensions of the proposed model for QQCA and simulation of basic gates, designing with this cell is quite optimal; it requires five cells in the design of the AND and OR gates and two cells in the design of the NOT gate. Based on the number of cells used in the basic gates, the total area in the AND and OR gates is 576 × 10 −6 µm 2 and in the NOT gate is 276 × 10 −6 µm 2 . The base gates are fully optimized and latency is equal to 0.25 clockcycle or 0.25 × 10 −12 s, which is reduced in comparison with prior works. Also, the power consumption of a cell in terms of quantum calculation and the proposed model is also investigated. Abstract : Quantum cellular automata (QCA) technology is an alternative technology to complementary metal oxide semiconductor (CMOS) in logic circuit design. In this paper, the quaternary QCA cell is examined using three particles for polarization, Hamiltonian matrix, and power consumption. Using the proposed cell, quaternary basic gates are designed and a simulator for designing quaternary circuits is presented, by which the basic gates are simulated and examined.